Piezoelectric enhancement under negative pressure - Alexander Kvasov (Nature Portfolio, 2016)
Recently, negative pressure has been observed in perovskite nanowires by annealing the wires from a lower-density phase. Here, the authors show that the negative pressure enhances the piezoelectric coefficient of PbTiO3 and Pb(Zr,Ti)O3 nanowires experimentally and by ab initiocalculations.